2011
DOI: 10.1159/000324054
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of the UV Filters Ethylhexyl Methoxycinnamate and Butyl Methoxydibenzoylmethane in Lipid Microparticles: Effect on in vivo Human Skin Permeation

Abstract: Background: Lipid microparticles loaded with the UVB filter ethylhexyl methoxycinnamate (EHMC) and the UVA filter butyl methoxydibenzoylmethane (BMDBM) were evaluated for their effect on the sunscreen agent’s percutaneous penetration. Methods: Microparticles loaded with EHMC or BMDBM were prepared by the melt emulsification technique using stearic acid or glyceryl behenate as lipidic material, respectively, and hydrogenate phosphatidylcholine as the surfactant. Nonencapsulated BMDBM and EHMC in conjunction wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 46 publications
3
17
0
Order By: Relevance
“…An emulsion with 10% water instead of DGME served as control formulation. The penetration of quercetin into human skin was studied in vivo using the tape stripping technique, based on the progressive removal of the stratum corneum outer layers by sequential stripping with adhesive tapes [29,30,36]. The amount of quercetin transferred to the individual tape strips following topical application of the tested formulations was quantified to provide the in vivo stratum corneum penetration profile of the flavonoid.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An emulsion with 10% water instead of DGME served as control formulation. The penetration of quercetin into human skin was studied in vivo using the tape stripping technique, based on the progressive removal of the stratum corneum outer layers by sequential stripping with adhesive tapes [29,30,36]. The amount of quercetin transferred to the individual tape strips following topical application of the tested formulations was quantified to provide the in vivo stratum corneum penetration profile of the flavonoid.…”
Section: Resultsmentioning
confidence: 99%
“…The creams were homogeneously distributed using rubber gloves. After an application time of 60 min [30], the remaining preparation was removed from the treated area by a cotton swab, and then the stratum corneum was sequentially stripped 15 times with Scotch transparent adhesive tapes [30,36,37]. The tapes were applied to the skin with a constant pressure by a 500 g stainless steel roller (30 mm diameter).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mike's group also showed that sunscreen products designed and marketed for application to children did not reduce sunscreen permeation compared to general-purpose sunscreen formulations [44]. These reports led to increased interest in the reformulation of sunscreen products to optimize activity at the skin surface and minimize skin penetration and systemic absorption both by Mike's group [45,46,47,48] and others [48,49,50,51]. …”
Section: Applied Science - Influencing Regulatory Perspectives and Inmentioning
confidence: 99%
“…Likewise for solid nanoparticles, the penetration pathways are still a topic of intensive investigation. In intact skin, it was demonstrated that topically applied solid nanoparticles are located only on the skin surface or within the upper lipid layers of the stratum corneum [15,16]. From here, the nanoparticles can be rapidly removed by washing processes, by textile contact or by desquamation [17].…”
Section: Introductionmentioning
confidence: 99%